2014 Power Systems Computation Conference 2014
DOI: 10.1109/pscc.2014.7038484
|View full text |Cite
|
Sign up to set email alerts
|

A relaxation scheme to combine phasor-mode and electromagnetic transients simulations

Abstract: Abstract-This paper deals with a new scheme for coupling phasor-mode and electromagnetic transients simulations. In each simulation, an iteratively updated linear equivalent is used to represent the effect of the subsystem treated by the other simulation. Time interpolation and phasor extraction methods adapted to this scheme are presented and compared to existing methods. Finally, simulation results obtained with a 74-bus test system are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…One issue tackled in this paper is the proper choice and update of the multi-port equivalent attached to those interface buses. This is an extension of the authors' previous work reported in [9], [10].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…One issue tackled in this paper is the proper choice and update of the multi-port equivalent attached to those interface buses. This is an extension of the authors' previous work reported in [9], [10].…”
Section: Introductionsupporting
confidence: 85%
“…It must be noted that the choice between Norton and Thévenin is arbitrary, as for each one there is an equivalent model in the other representation. This approach can be already found in [13], while further investigations have been reported in [7], [9], [10]. Nevertheless, the above references report on results with a single boundary bus, and on small test systems.…”
Section: A Short Review Of Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the system basically reaches steady state at t = 12 s, and the EMT model and the TSA model of the same sub-network at steady state are equivalent. Through analyzing the simulation results, it can be seen that, although a serious three-phase short-circuit fault occurs at the boundary of the area of interest, the average difference [31] of the voltages at the fault points and the average difference of rotor speed are all within 0.05 pu. It is proven that the proposed method can ensure that the area of EMT simulation is flexibly changed and meets the requirements of simulation accuracy.…”
Section: B Case Twomentioning
confidence: 99%
“…Previous researches on EMT and transient stability co‐simulation were mainly focused on interfacing techniques [810], interaction protocols [10, 11], and development of co‐simulation programs [11–13]. The external network equivalents used in these researches were developed based on positive‐sequence network models, which would undermine the merits of co‐simulation.…”
Section: Introductionmentioning
confidence: 99%